2022
DOI: 10.1108/sjls-11-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

The use of web-based translation software in translating religious terms

Abstract: PurposeThe integration of the Internet in translation creates several opportunities for translators. This study aims at examining the impact of using web-based translation (WBT) on translating religious texts.Design/methodology/approachThe study followed a quasi-experimental study design. Sixty students enrolled in English Department, University of Bisha, participated in this study. The participants were divided randomly into three groups (i.e. words group, sentences group and passages group). The data was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some studies were conducted to explore the extent to which the Internet influences the process of translation. For example, Mahdi (2022) examined the incorporation of web-based translation (WBT) on translating religious texts. The results indicated that WBT was more beneficial in translating words than translating sentences or passages.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Some studies were conducted to explore the extent to which the Internet influences the process of translation. For example, Mahdi (2022) examined the incorporation of web-based translation (WBT) on translating religious texts. The results indicated that WBT was more beneficial in translating words than translating sentences or passages.…”
Section: Review Of Literaturementioning
confidence: 99%